2020
DOI: 10.3389/fonc.2020.00990
|View full text |Cite
|
Sign up to set email alerts
|

RIG-1-Like Receptor Activation Synergizes With Intratumoral Alpha Radiation to Induce Pancreatic Tumor Rejection, Triple-Negative Breast Metastases Clearance, and Antitumor Immune Memory in Mice

Abstract: Diffusing alpha-emitting radiation therapy (DaRT) employs intratumoral Ra-224-coated seeds that efficiently destroy solid tumors by slowly releasing alpha-emitting atoms inside the tumor. In immunogenic tumor models, DaRT was shown to activate systemic antitumor immunity. Agonists of the membrane-bound toll-like receptors (TLRs) enhanced these effects and led to tumor rejection. Here, we examined the combination of DaRT with agents that activate a different type of pattern recognition receptors, the cytoplasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“… 458 The latest research shows that activating RIG-I before diffusing alpha-emitting radiation therapy for metastatic and low immunogenic tumors is a more effective combination therapy technique that can inhibit tumor growth and metastasis. 459 …”
Section: Clinical Therapy Of Prrsmentioning
confidence: 99%
“… 458 The latest research shows that activating RIG-I before diffusing alpha-emitting radiation therapy for metastatic and low immunogenic tumors is a more effective combination therapy technique that can inhibit tumor growth and metastasis. 459 …”
Section: Clinical Therapy Of Prrsmentioning
confidence: 99%
“…Another study has demonstrated synergistic inhibition of tumor growth and enhanced induction of long-term immune memory cells in murine mammary and pancreatic carcinoma models using a combination of poly(I:C) injection with transplantation of alpha-emitting radiation seeds into the tumor [40], an experimental treatment approach that is currently tested in clinical trials (e.g., NCT-04377360, NCT-03353077, NCT-03015883). In contrast, in our approach, a clinical linear accelerator has been used, which is standard clinical practice and is therefore directly applicable in routine clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…Poly (I:C), both with or without PEI, prior to DaRT retarded the growth of the tumors and elicited specific anti-tumor activity. Treatments with a T-regulatory cell inhibitor or the epigenetic drug, decitabine, intensified the anti-tumor manifestations of the combination of DaRT and poly (I:C)-PEI and extended survival rates due to lung metastasis clearance [ 66 ].…”
Section: Potentiation Of Particle-radiation-mediated Anti-tumor Immentioning
confidence: 99%